What determines content? : the internalism/externalism dispute - Marvan, Tomáš (Cambridge Scholars Press, 2006)
A distinguished team of fourteen European philosophers addresses the current debates on internalism versus externalism in the philosophy of language and mind. The main objective of the volume is to demonstrate the philosophical significance and fruitfulness of the internalism/externalism debate on a wide range of issues, and to do so in a manner which is sophisticated yet accessible to non-specialists. The issues authors deal with include linguistic deference, interpreting classical externalist thought-experiments by Putnam and Burge, the nature of Wittgenstein's externalism, apriority, intersubjective externalism, and object-dependence of thought and temporal externalism. Some of the contributors try to strike a balance between internalist and externalist position.